a ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KAMPUNG SUKAN TENGAH - Darmono, Darmono (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2019)
ABSTRACT This study aims to determine the factors that influence the production of rice farmers in Central Sukan Village, Sambaliung District. Furthermore, this research is expected to be useful as input and consideration for the Berau District Government to determine strategies and programs in the development of rice food crops in Berau District. The analysis tool used is by using the Coob Douglas Function and through regression and correlation analysis which is then tested using the F Test. Based on the results of data analysis that has been done, it can be seen that the effect of land and capital usage on the production of paddy farmers in Central Sukan village using regression analysis is obtained by the equation: Y = 0.0452 + 0.0016 X2 + 1.3810 X3. Furthermore, it is stated in the Cobb Douglass production function as follows: Qi = 0.0443 Li (0.0016) Ki (1,3810) This equation shows that every addition to the Land Area factor will have an influence on increasing Paddy Farmer Production in Central Sukan Village. Likewise, the addition of working capital will have an influence on increasing Paddy Farmer Production in Central Sukan Village. Then the results of the calculation in hypothesis testing with the F (Fh) test are compared with the F value in the table (Ft) with free degrees 2 and 7, so that the Ft value is 4.74. because F count (175) is greater than F table, the hypothesis proposed by the author is accepted. In this case, the area of ​​land and capital together have a significant effect on the production of farmers at a confidence level of 95%. The correlation coefficient from the results of the analysis is 0.99 means that each addition of land area and capital will be followed by the addition of production proportionally and vice versa. The coefficient of determination shows a value of 0.98 or 98% of the variation in fluctuations in the production of farmers in Central Sukan village influenced by land area and capital factors. While the remaining 0.02 percent is influenced by other factors that are outside the model.   Keywords: Land Area, Capital, Production   ABSTRAK Penelitian ini bertujuan untuk mengetahui faktor yang mempengaruhi produksi petani padi di Kampung Sukan Tengah Kecamatan Sambaliung. Selanjutnya penelitian ini diharapkan berguna sebagai bahan masukan dan pertimbangan bagi Pemerintah Kabupaten Berau guna menentukan strategi dan program dalam pengembangan tanaman pangan padi di Kabupaten Berau. Alat analisis yang digunakan yaitu dengan menggunakan Fungsi Coob Douglas dan melalui analisis regresi dan korelasi yang selanjutnya diuji dengan menggunakan Uji F. Berdasarkan hasil analisis data yang telah dilakukan, maka dapat diketahui bahwa pengaruh penggunaan Luas Lahan dan Modal terhadap Produksi Petani  Padi di Kampung Sukan Tengah dengan menggunakan analisis regresi diperoleh persamaan : Y  =  0,0452 + 0,0016  X2 + 1,3810 X3. Selanjutnya dinyatakan dalam fungsi produksi Cobb Douglass sebagai berikut : Qi = 0,0443 Li (0,0016) Ki (1,3810) Persamaan tersebut menunjukkan bahwa setiap terjadi penambahan faktor Luas Lahan maka akan memberikan pengaruh terhadap peningkatan Produksi Petani Padi di Kampung Sukan Tengah. Demikian pula penambahan Modal kerja akan memberikan pengaruh terhadap peningkatan Produksi Petani Padi di Kampung Sukan Tengah. Selanjutnya hasil hitungan dalam pengujian hipotesis dengan uji F (Fh) dibandingkan dengan nilai F pada tabel (Ft) dengan derajat bebas 2 dan 7, sehingga diperoleh nilai Ft sebesar 4,74. karena F hitung (175) lebih besar dari F tabel maka hipotesis yang diajukan penulis diterima. Dalam hal ini bahwa Luas Lahan dan Modal secara bersama-sama berpengaruh signifikan terhadap Produksi Petani pada tingkat keyakinan sebesar 95%. Koefisien korelasi dari hasil analisis adalah 0,99 berarti bahwa setiap penambahan Luas Lahan dan Modal akan diikuti dengan penambahan Produksi secara proporsional demikian pula sebaliknya. Koefisien determinasi menunjukkan nilai 0,98 atau 98% variasi naik turunnya Produksi Petani di Kampung Sukan Tengah dipengaruhi oleh faktor Luas Lahan dan Modal. Sedangkan sisanya sebesar 0,02 persen adalah dipengaruhi oleh faktor lain yang berada diluar model.   Kata Kunci : Luas Lahan, Modal, Produksi